Clinical diagnosis of seasonal influenza by physicians: a retrospective observational study. Issue 7 (22nd July 2022) - Maita, Hiroki; Kobayashi, Tadashi; Akimoto, Takashi; Matsuoka, Fumihiko; Funakoshi, Shigeki; Osawa, Hiroshi; Kato, Hiroyuki
Abstract : Objective: To elucidate the diagnostic accuracy of pretest probability of influenza (%) by physicians and the factors affecting the clinical diagnosis. Design: Retrospective, single-centre observational study. Setting: A community primary care clinic in Japan. Participants: The participants were recruited from a database of studies conducted during the influenza season from December 2017 to April 2019. Primary outcome measure: Sensitivity and specificity of the physician's clinical diagnosis of influenza recorded in the medical record as pretest probability. Results: A total of 335 patients (median age, 31 years; male, 66.6%) were analysed in this study. The area under the curve (AUC) of the physician's pretest probability was 0.77. At a cut-off value of 30%, the sensitivity and negative likelihood ratio were 92.0% (95% CI 86.7 to 95.7) and 0.19 (95% CI 0.11 to 0.33), respectively. At a cut-off value of 80%, the specificity and positive likelihood ratio were 90.8% (95% CI 85.4 to 94.6) and 4.01 (95% CI 2.41 to 6.66), respectively. The AUCs of patients who had and had not taken any medications before visiting the clinic were 0.77 (95% CI 0.69 to 0.85) and 0.78 (95% CI 0.71 to 0.84), respectively. The AUCs of patients with type A and B influenza were 0.78 (95% CI 0.72 to 0.84) and 0.76 (95% CI 0.70 to 0.82), respectively. The AUCs of vaccinated and unvaccinated patients were 0.80 (95% CI 0.72 to 0.88) and 0.76 (95% CI 0.63 to 0.89), respectively. The AUC for patients less than 12 hours after onset was 0.69 (95% CI 0.51 to 0.88), and that for patients aged younger than 6 years was 0.69 (95% CI 0.49 to 0.88). Conclusions: The physician's pretest probability of influenza (%) may be useful for both definitive and exclusionary diagnoses within the limits of our study.